2013
DOI: 10.1007/s00726-013-1606-x
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of post-translational modified amino acids as an approach to increase both chemical and biological diversity of conotoxins and conopeptides

Abstract: Bioactive peptides from Conus venom contain a natural abundance of post-translational modifications that affect their chemical diversity, structural stability, and neuroactive properties. These modifications have continually presented hurdles in their identification and characterization. Early endeavors in their analysis relied on classical biochemical techniques that have led to the progressive development and use of novel proteomic-based approaches. The critical importance of these post-translationally modif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 123 publications
0
22
0
Order By: Relevance
“…Random oxidation of the ligated HwTx‐I produced 10 out of the 16 possible disulfide isomers (Supporting Information Figure S2). Our goal here was to produce as many isomers as possible and to examine the potential for alternative structures that could have demonstrated bioactivity.…”
Section: Discussionmentioning
confidence: 99%
“…Random oxidation of the ligated HwTx‐I produced 10 out of the 16 possible disulfide isomers (Supporting Information Figure S2). Our goal here was to produce as many isomers as possible and to examine the potential for alternative structures that could have demonstrated bioactivity.…”
Section: Discussionmentioning
confidence: 99%
“…These facts show that post-translational modifications in α-conotoxins can interfere in conotoxin/nAChR interactions. Indeed, it was suggested that amidation promotes native folding in this toxin group, leading to their selectivity [26]. Previous experiments showed that the proline from the m -loop and C-terminal amidation in α- and χ-conotoxins act as conformational switches [69].…”
Section: Conotoxins Interacting On Nicotinic Acetylcholine Receptomentioning
confidence: 99%
“…Conotoxins’ structural properties seem to be important for target interaction [25]. Importantly, other features are present in natural conotoxins such as the location of key amino acids on their primary sequence [5] and post-translational modifications, including amidation, sulfation, pyroglutamylation, γ-carboxylation, hydroxylation, O-glycosylation, and bromination [26]. On the whole, these features must be considered when analyzing conotoxin/target interaction.…”
Section: Introductionmentioning
confidence: 99%
“…Conotoxins contain numerous Post-translational Modifications [17]. These PTMs are responsible for phyla and receptor selectivity.…”
Section: Future Direction For Conotoxin Regulation -Bioengineered Conmentioning
confidence: 99%
“…These structural features are stabilized by disulfide bonds generated from the abundance of cysteine moieties in its primary structure [1,4]. Interestingly, these Cys residues are found in predictable locations within a conotoxin's sequence, giving rise to loops of known amino acid lengths, which influence their bioactivity [4,5]. Conotoxins can contain anywhere from one to five disulfide bonds which typically produce intramolecular connections [6].…”
Section: Introduction To Conotoxinsmentioning
confidence: 99%